“ESTUDIO COMPARATIVO DE LA CALIDAD DE SNACKS ELABORADOS A PARTIR DE SEMILLAS DE ZAMBO (Cucurbita Ficifolia B) Y SEMILLAS DE GIRASOL (Helianthus Annuus L)”. - Zambrano Zambrano, Jean Carlos (2019)
The objective of the following titration work was to carry out a comparative study of the quality of snacks made from seeds of zambo (Cucurbita Ficifolia B) and sunflower seeds (Helianthus Annuus L), where quality parameters such as; moisture, ash, fats, protein, fiber and nitrogen-free elements that determined the percentage (%) composition of the two seeds, physical chemical aspects of each of the oils of zambo and sunflower were evaluated where they conducted studies of the relative density , iodine index, peroxides, acidity, refraction and saponification. the study of the bromatological characteristics determining the types of fatty acids that the zambo oil possesses by means of chromatography to be compared with the sunflower oil and to determine the quality of the same ones. A microbiological study of the raw materials and snacks made from the seeds of zambo and sunflower was carried out, to finally carry out a sensory and acceptance analysis in the snacks made from zambo seeds. For the analysis of all the data, a variance study (ANOVA) with Tukey test (p <0.05) was applied. The study concluded that the seeds of zambo are nutritious and can be used in finished products and the derivatives of the seeds, since for its essential characteristics of protein, essential fatty acids and carbohydrates this food has the potential to be used commercially in the field of the agro-industry for the elaboration of snacks and other types of finished products.